Comparison Between Bs 5950 And Eurocode 3 For The Design Of Pre-Engineered Steel Structure Of A Factory - Chuah, Hoi Ching (Universiti Sains Malaysia, 2018)
The aim of this project dissertation is to design selected pre-engineered steel structural members including rafter and column with non-typical section by using two different design standards which are British Standard 5950 (BS 5950-1-1: 2000 “Code of Practice for Design – Rolled and Welded sections”) and Eurocode 3 (MS EN 1993-1-1: 2010 “General rules and rules for buildings”. The advantages and disadvantages of design using Eurocode 3 including cost effectiveness of the design compared with BS 5950 are determined in this project dissertation. The findings show that design using Eurocode 3 experienced lower structural performance in initial analysis but higher in final analysis compared to design using BS 5950 for critical combination. The structural capacities of Eurocode 3 design including shear capacity, axial capacity and moment capacity for the section used in this analysis are higher than BS 5950 design. Although the stable length for haunch in Eurocode 3 design is longer than BS 5950 design, the structural stability of Eurocode 3 design including the resistance of lateral torsional buckling and resistance of buckling due to interaction of axial and bending moment are lower compared to BS 5950 design. Lastly, Eurocode 3 design consumes 0.88% more still weight than BS 5950 design. This is because larger section sizes are required for Eurocode 3 to fulfill all requirements. Therefore, it can be concluded that BS 5950 design is cheaper than Eurocode 3 design.